(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Over the last two years, the educational landscape has shifted dramatically. The educational system worldwide was also impacted by the Carona. The effects of Carona on elementary, secondary, and tertiary education have been devastating. The academic community’s administrators, teachers, and students suffer from lost time, are unable to attend regularly scheduled classes, and are unable to administer and take examinations.